Leprosy: A Review of Epidemiology, Clinical Diagnosis, and Management - Kou-Huang Chen; Cheng-Yao Lin; Shih-Bin Su; Kow-Tong Chen (Journal of Tropical Medicine)
Leprosy is a neglected infectious disease caused by acid-fast bacillus Mycobacterium leprae. It primarily affects the skin and then progresses to a secondary stage, causing peripheral neuropathy with potential long-term disability along with stigma. Leprosy patients account for a significant proportion of the global disease burden. Previous efforts to improve diagnostic and therapeutic techniques have focused on leprosy in adults, whereas childhood leprosy has been relatively neglected. This review aims to update the diagnostic and therapeutic recommendations for adult and childhood leprosy. This review summarizes the clinical, bacteriological, and immunological approaches used in the diagnosis of leprosy. As strategies for the diagnosis and management of leprosy continue to develop better and more advanced knowledge, control and prevention of leprosy are crucial.